New cyclopentaquinoline hybrids with multifunctional capacities for the treatment of Alzheimer's disease - Kamila Czarnecka; Małgorzata Girek; Karolina Maciejewska; Robert Skibiński; Jakub Jończyk; Marek Bajda; Jacek Kabziński; Przemysław Sołowiej; Ireneusz Majsterek; Paweł Szymański (Taylor & Francis Group, 2018)
Alzheimer's disease (AD) is the most common progressive form of brain neurodegeneration and the most prevailing cause of dementia. Unfortunately, the aetiology of AD is not completely studied but different factors are associated with the development of AD such as among others low level of acetylcholine, aggregation of β-amyloid (Aβ), hyperphosphorylated tau protein, oxidative stress, and inflammation. The study encompass organic syntheses of 2,3-dihydro-1H-cyclopenta[b]quinoline with 5,6-dichloronicotinic acid and suitable linkers derivatives as multifunctional agents for AD treatment. Afterwards self-induced amyloid beta aggregation, inhibition studies of acetylcholinesterase and butyrylcholinesterase and molecular docking studies were performed. The results showed that 3b compound exhibited the best acetylcholinesterase inhibitory activity, with IC50 value of 0.052 µM which is lower compared to references. Besides, all synthesised compounds showed good butyrylcholinesterase inhibitory activity with IC50 values from 0.071 to 0.797 µM. Compound 3b exhibited strong Aβ1-42 aggregation inhibitory effect with 25.7% at 5 µM to 92.8% at 100 µM as well as good anti-inflammatory effect. Thus, new compounds could create new perspectives for further development as a multi-target-directed agent for AD treatment.